Budaya Politik Pemilih Muda Menjelang Pilkada Serentak Tahun 2024 Di Kecamatan Paguyaman Pantai Kabupaten Boalemo - Nurdin, Ais; Sadam Nurdin; Mais Nurdin; Jois Nurdin (Jurnal Dinamika Sosial Budaya, 2025)
This research aims to discuss the political culture of young voters ahead of the 2024 simultaneous regional elections in Paguyaman Pantai District, Boalemo Regency. In this research, researchers used qualitative methods with a descriptive approach. In this research, data is obtained through observation, interviews and documentation so that the data obtained is in accordance with the facts that occur in the field. The research results show that parochial political culture means young voters have low political awareness in determining their political rights. Then the political culture of Kaula is characterized by relatively high political awareness, but on average young voters still follow the choices of their parents or people who have influence. This is due to the lack of information obtained by young voters so that the level of knowledge of young voters is low.